Detection of adulterations in native stingless bees honey from Argentina using UV–Vis spectroscopy coupled with chemometrics - Marcinkevicius, Karenina; Gennari, Gerardo Pablo; Salomon, Virginia María; Vera, Nancy Roxana; Maldonado, Luis Maria (Springer, 2025)
Stingless bee honeys are appreciated in the world market due to their nutritional and biological properties. In Argentina, the most commercially exploited species of stingless bee is Tetragonisca fiebrigi whose honey is the only one of its kind incorporated into the Argentine Food Code. The value of stingless bee honeys has been increasing in recent years, making them more prone to adulteration. However, there are no methodologies available to perform adequate controls to verify their authenticity. Therefore, the objective of this work was to develop and validate a UV–Vis spectroscopy and chemometric combined methodology to detect and quantify adulterations of Tetragonisca fiebrigi honeys produced in Argentina. The adulterants analyzed included Apis mellifera honey, three commercial sugar syrups (glucose, extra glucose, maltodex40) and three laboratory-formulated sugar syrups (sucrose, fructose and high fructose). The results showed that through principal component analysis it is possible to differentiate pure honey from adulterated honey. Through linear discriminant analysis and partial least squares regression, unknown mixtures could be classified by determining the degree of adulteration and identifying the type of adulterant used. The method allows detecting the addition of up to 64% of Apis mellifera honey, while the maximum amount of detectable added syrup varies between 51 and 70%, depending on the type of syrup.